A night divided ebook - Nielsen, Jennifer A. (2015)
From NYT bestselling author Jennifer A. Nielsen comes a stunning thriller about a girl who must escape to freedom after the Berlin Wall divides her family between east and west. A Night Divided joins the Scholastic Gold line, which features award-winning and beloved novels. Includes exclusive bonus content!With the rise of the Berlin Wall, Gerta finds her family suddenly divided. She, her mother, and her brother Fritz live on the eastern side, controlled by the Soviets. Her father and middle brother, who had gone west in search of work, cannot return home. Gerta knows it is dangerous to watch the wall, yet she can't help herself. She sees the East German soldiers with their guns trained on their own citizens; she, her family, her neighbors and friends are prisoners in their own city.But one day on her way to school, Gerta spots her father on a viewing platform on the western side, pantomiming a peculiar dance. Gerta concludes that her father wants her and Fritz to tunnel beneath the wall, out of East Berlin. However, if they are caught, the consequences will be deadly. No one can be trusted. Will Gerta and her family find their way to freedom?